The Influence Of The Use Of Information Technology And Competence On Employee Performance At The Population And Civil Registry Service Of Pagar Alam City - Yadi Maryadi; Umi Narimawati; M. Yani Syafei (UNIVED Press, 2024)
This research aims to determine the influence of information technology and competency on employee performance at the Pagar Alam City Population and Civil Registry Service. The dependent variable in this research is Employee Performance (Y) and the independent variables are Information Technology (X1) and Competency (X2). The population and research sample were 50 employees at the Population and Civil Registry Service of Pagar Alam City. The data obtained were analyzed using the PLS (Partial Least Square) analysis technique via SmartPLS Software and the SPSS 26 application. Where it was partially processed using the PLS analysis technique while it was simultaneously processed using the SPSS 26 application. Based on the research results it can be concluded that: (1) Information technology positive and significant effect on employee performance; (2) Competency has a positive and significant effect on employee performance; (3) simultaneously, information technology and competence have a positive and significant effect on employee performance.